RESPON PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) DENGAN PEMBERIAN PUPUK HAYATI Bio-Extrim PADA BERBAGAI MEDIA TANAMAN - Aidi Daslin Sagala; Sri Utami; Abdul Suhendra Damanik (AGRIUM: Jurnal Ilmu Pertanian, 2011)
AbstractGrowth response of Cocoa Seed (Theobroma cacao L.) has been conducted with provision of Bio-Fertilizer Biological extreme Planting In Various Media, using a randomized block design (RBD) factorial with two factors. The first factor is the various types of growing media M0: Soil Topsoil, M1: Land Topsoil + cow manure (1: 1), M2: Land Topsoil Compost + (1: 1). The second factor of liquid biological fertilizer (Bio-extreme) is E0: no treatment (control), E1: 5 cc / liter of water, E2: 10 cc / liter of water. Observation parameters of plant height (cm), number of leaves (pieces), stem diameter (mm), leaf area (cm), wet weight of the top and bottom of the plant (crown and root) (g). M2 treatment DMRT test results (soil + Compost Topsoil) showed an increase in plant growth 12MSPT age. Treatment of biological fertilizers and Bio-extreme (E) E2 treatment (10 cc / liter of water)) showed an increase in plant growth 12MSPT age. The interaction between M x E showed no obvious effect on all parameters of the observations. Visual enhancement of plant growth was obtained on treatment M2E2.Keywords: growth response, cocoa,bio-feltilizer, bio-extrim